Obligation to co-operate for electronic communications service providers in criminal proceedings in practice (Academic Journal of Internal Affairs, 2018)
In the light of recent legislative amendments, this author provides an overview of data processing obligations of electronic communications service providers for law enforcement purposes in Hungary.
Keywords: data processing; electronic communication; criminal proceeding